Outcome of patients on second line antiretroviral therapy under programmatic condition in India - Chakravarty, Jaya (BMC Infect Dis, 2015)
BACKGROUND: The National AIDS Control Organization of India has been providing free second line antiretroviral therapy (ART) since 2008. This observational study reports the survival and virologic suppression of patients on second-line ART under programmatic condition and type of mutations acquired by those failing therapy. METHODS: 170 patients initiated on second-line therapy between 2008 and 2012 were followed up till 2013. Viral Load (VL) was repeated at 6 months for all patients and at 12 months for those with VL >400 copies/ml at 6 months. Adequate virological response was defined as plasma HIV-1 VL <400 copies/ml and virological failure was defined as VL >1000 copies/ml. Genotyping was done in 16 patients with virological failure. RESULTS: Out of 170 patients, 110 (64.7 %) were alive and on therapy and 35 (20.5 %) expired. In the first year the occurrence of death was 13.7 /100 person years while between1 and 5 year it was 3.88 /100 person years. In the first year, duration of immunological failure >12 months, weight <45 kg, WHO clinical stage 3 and 4 and WHO criteria CD4 count less than pretherapy baseline [hazard ratio HR 4.2. 15.8, 11.9 & 4.1 respectively] and beyond first year poor first and second line adherence and first line CD4 count < 200/μL [HR 5.2,15.8, 3.3 respectively] had high risk of death. 119/152 (78.2 %) had adequate virological response and 27/152 (17.7 %) had virological failure. High viral load at baseline and poor second line adherence (Odds Ratio 3.4 & 2.8 respectively) had increased risk of virological failure. Among those genotyped, 50 % had major Protease Inhibitor mutation (M46I commonest) however 87.5 % were still susceptible to darunavir. CONCLUSIONS: Second line therapy has shown high early mortality but good virological suppression under programmatic conditions.